Use of selfie sticks and iPhones to record operative photos and videos in plastic surgery - Ashok Basur Chandrappa; Pradeep Kumar Nagaraj; Srikanth Vasudevan; Anantheswar Yelampalli Nagaraj; Krithika Jagadish; Ankit Shah (Indian Journal of Plastic Surgery)
Use of smartphone has become ubiquitous. With smartphone cameras becoming powerful, they are replacing digital cameras and digital SLRs as primary instruments to take photos and record videos. It is natural even for plastic surgeons that smartphones are handy to take still photographs and even record high-definition or 4K videos. Another invention which has become popular with smartphone photography is a selfie stick. We explain the possibility and methodology of using an iPhone and selfie stick to take operative photographs and high-quality videos.